Lower plate serpentinite diapirism in the Calabrian Arc subduction complex - A. Polonia (Nature Portfolio, 2017)
Understanding subduction zone mechanics and resulting volcanism remains challenging. Here, the authors present seismic reflection profiles from the Mediterranean Sea where serpentinite diapirs are present on the external subduction system of the Calabrian Arc and may be linked to recent volcanism at Etna.